Agroecosystem Degradation Evaluation of Broccoli (Brassica oleracea) Farm Using Some Biotic Indices in Batu, East Java, Indonesia - Lina Mariantika; Catur Retnaningdyah; Endang Arisoesilaningsih (Indonesian Journal of Environment and Sustainable Development, 2019)
The aim of this study was to evaluate the degradation of broccoli agroecosystem in Batu caused by a longterm of intensive farming and of synthetic chemical exposure using some biotic indices. Evaluation covered on quality of habitat, biodiversity, and environmental services in three organic and intensive farm, each Batu, Bumiaji, and Junrejo Regencies, using five repetitions in each location. Habitat quality was evaluated by measuring the soil organic matter, water irrigation and soil suspension pH, electric conductivity, and water turbidity in situ. Biodiversity quality was evaluated by determining the score of Importance Value Index (IVI), Shannon-Wiener Diversity Index (H’) and Margalef’s Richness Index (R) soil fauna using handsorting within the area of l m2, as well as refugial vegetation. Environmental service quality was evaluated by scoring using the Ecosystem Integrated Assessment (EIA). The data were analyzed statistically using Principal Component Analysis (PCA). The result showed that soil organic matter and pH were obviously higher, while the irrigation water was less turbid in organic farming rather than the intensive one. Furthermore, the H’ and R indices proved that biodiversity quality in organic farming field was higher (H’ score 1.4-1.9 and R 3.5-4.0) comparing to those of intensive farming (H’ score 0.6-0.9 and R 1.2-1.6). Whereas, the ecosystem service based on EIA index revealed that the organic agroecosystem showed a fair to good quality with the score 3.0-4.3. It was higher than those of intensive farming which was classified as poor to fair with the score 1.7-2.8. Therefore, the organic broccoli agroecosystem in Batu provided a better habitat for biodiversity conservation and greater the environmental service as a sustainable farming system.Key words: Agroecosystem, Biodiversity, Ecological services, Intensive, Organic